Seeking excellence in higher education teaching: challenges and reflections seeking excellence in higher education teaching: challenges and reflections / Wayne L. Edwards - Edwards, Wayne L. (Universiti Teknologi MARA, 2018)
While fully understanding the multi-faceted role of universities and other higher education institutions, Professor Edwards advocates for the status and value of teaching, particularly in times of emphasis on research outputs and league tables. He draws on his reflections from more than four decades of experience of teaching at university level plus involvement in teaching development, including his views on what makes a good teacher and a set of principles of good teaching. His views are shared on culture and evaluation as key parts of successful teaching. The final section of the paper presents a case study of his support of teaching in the past nine years as President of a privately owned international tertiary institution in New Zealand. The paper concludes with a battery of questions for conference participants’ own reflections on teaching. Of course, he recognises the importance (and competing pressures) of teaching, research, service and administration in the lives of today’s academics.